Features of the Debut as an Early Predictor of The Clinical Prognosis of Schizophrenia with An Episodic A Type of Course (Texas Journal of Medical Science, 2023)
The aim of the study was to determine the prognostic significance of the features of the debut of schizophrenia for the social and labor prognosis at the remote stages of the disease. The results of the study allowed us to establish that the acute onset of the disease at the age of over 20 years are favorable factors for the social and labor prognosis of patients with paroxysmal schizophrenia. Early onset of the disease at the age of 20 years with initial disorders, on the contrary, play the role of unfavorable factors that worsen the prognosis as the disease progresses.